Drug-related problems observed in a pharmaceutical care service, Belo Horizonte, Brazil (Brazilian Journal of Pharmaceutical Sciences, 2009)
This present observational, longitudinal, and non-concurrent study was developed with the purposes of evaluate the profile of patients attended by a pharmacotherapeutic follow-up service and describe the Drug-Related Problems (DRPs) found over there; determine the proportion of DRPs between the health problems presented by the studied population, classifying them and identifying the situations related with their appearance. The study was developed at the School Pharmacy of Newton Paiva University Center, Belo Horizonte, MG, during the period from 2001 November up to 2003 November. Ninety seven patients have been evaluated, the majority of female sex (66.0%), with up to 8 years of scholarship (45.4%), mean age of 56.7 ± 13.0 years; mean of 4 ± 2 diagnosed diseases; 7 ± 6 complaints and 4 ± 2 medications per patient. Nine hundred and twelve health problems have been identified: 56.5% uncontrolled. From the uncontrolled problems, 380 (73.6%) were DRPs and between these, 81 (21.3%) were risks for DRP. From the 97 followed-up patients, 89 (91.7%) have presented at least one DRP during the follow-up. The more frequent DRPs were related to effectiveness (53.2%), to necessity (25.2%) and to safety (21.6%). A great number of uncontrolled problems was observed, as well as the possibility to resolve them by means of pharmaceutical care, indicating so the resolutive potential of this practice.